Next-Gen Learning: Implementing Cooperative Game-Based Learning to Enhance Learning Effectiveness - Juniarti, Cahaya; Putra, Tarekh Febriana; Gufron, Hilman (Media Komunikasi FPIPS, 2025)
This study aims to evaluate the effectiveness of CGBL in enhancing learning outcomes. The integration of GBL with the TGT model was applied to combine interactivity, collaboration, and structured educational competition. Learning effectiveness was assessed using the ARCS model (Attention, Relevance, Confidence, Satisfaction), combined with additional indicators of AS and PIS. A quasi-experimental method with a non-equivalent control group design was employed, involving two D4-level student classes at Politeknik Negeri Bandung, assigned as the experimental group (CGBL) and the control group (conventional instruction). Data were collected through pretest and posttest to measure cognitive achievement, as well as a motivation questionnaire based on the ARCS model. Data were analyzed using t-tests and Mann–Whitney U tests to examine differences in learning outcomes, and Partial Least Squares–Structural Equation Modeling (PLS-SEM) was used to assess the validity and influence of motivational constructs. The findings show that the implementation of CGBL significantly improves students’ cognitive achievement, motivation, and participation compared to conventional methods (p < 0.05). The relevance construct was found to be the primary trigger for attention, confidence, and satisfaction, which in turn positively influenced both AS and PIS. These results confirm that integrating CGBL not only enhances learning engagement and satisfaction but also contributes to the development of students’ analytical and participatory competencies. This study offers theoretical contributions through the development of a motivation-based instructional model and provides practical solutions for innovative teaching strategies in higher education in the digital era.